Strategi Guru Pada Keberagaman Agama Dalam Membentuk Sikap Toleransi Antar Peserta Didik - Nor Azizah; Ahmad Suriansyah; Arta Mulya Budi Harsono; Bagus Aulia Iskandar; Mubarok (CV. ITTC INDONESIA, 2024)
This research aims to describe and analyze the religious diversity that exists at the Hippindo Banjarmasin Foundation Elementary School in creating an attitude of tolerance among students. Tolerance in diversity between teachers and students at the Hippindo Banjarmasin Foundation Elementary School is very well established. Researchers used qualitative methods in this research, while the approach used a case study approach. Data was obtained through interviews and observation. The research subjects here are school principals, teachers and students at school. This research identifies various approaches used by teachers, such as collaborative learning, introducing diversity well and showing good examples and habits, using interesting learning strategies, and holding programs that can support students' attitudes of tolerance. The results of this research show that The role of the teacher is very crucial when creating an inclusive and harmonious learning environment so that a good attitude of tolerance can be created between students and teachers.